2022
DOI: 10.3389/fendo.2022.783823
|View full text |Cite
|
Sign up to set email alerts
|

27-Hydroxycholesterol, The Estrogen Receptor Modulator, Alters DNA Methylation in Breast Cancer

Abstract: 27-hydroxycholesterol (27-HC) is the first known endogenous selective estrogen receptor modulator (SERM), and its elevation from normal levels is closely associated with breast cancer. A plethora of evidence suggests that aberrant epigenetic signatures in breast cancer cells can result in differential responses to various chemotherapeutics and often leads to the development of resistant cancer cells. Such aberrant epigenetic changes are mostly dictated by the microenvironment. The local concentration of oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
0
12
1
Order By: Relevance
“…27-HC inhibits the uptake and synthesis of FA and cholesterol by inhibiting the SREBP pathway and activating the liver X receptor (LXR) pathway 106 . In contrast, 27-HC can competitively inhibit the effect of estrogen because of its selective estrogen receptor (ER) regulatory function and promotes the proliferation of high-ER-expressing tumor cells, such as breast and ovarian cancer cells 107 . It can also induce an increase in GPX4 expression, thereby protecting tumor cells from ferroptosis.…”
Section: Landscape Of Abnormal Lipid Metabolism In Tumorsmentioning
confidence: 99%
“…27-HC inhibits the uptake and synthesis of FA and cholesterol by inhibiting the SREBP pathway and activating the liver X receptor (LXR) pathway 106 . In contrast, 27-HC can competitively inhibit the effect of estrogen because of its selective estrogen receptor (ER) regulatory function and promotes the proliferation of high-ER-expressing tumor cells, such as breast and ovarian cancer cells 107 . It can also induce an increase in GPX4 expression, thereby protecting tumor cells from ferroptosis.…”
Section: Landscape Of Abnormal Lipid Metabolism In Tumorsmentioning
confidence: 99%
“…Nevertheless, whether aberrant epigenome contributes to 27‐HC–mediated cellular and morphological changes and breast cancer progression is unknown. We had earlier reported that 27‐HC induces DNA methylation changes in subsets of genes in breast cancer cells 17 . In this study, 27‐HC–mediated changes in histone methyltransferases in breast cancer cells were investigated.…”
Section: Introductionmentioning
confidence: 91%
“…As DNMT3b (de novo methyl transferase) methylates previously unmethylated sites, E2 may alter the methylation pattern at the promoter region of several genes and their expression during long-term memory formation. Several studies showed that E2 not only increased the expression of DNMT3b but also its activity (Vini et al, 2022 ). E2–ER complex recruits several chromatin modifiers such as histone deacetylase (HDAC) 1 and the repressor complex known as polycomb complex 2 (PRC2) at the ERE.…”
Section: E2-mediated Epigenetic Modificationsmentioning
confidence: 99%